Development of principles of binary relations in the theory of economic management - Dotsenko, Sergiy (Technology audit and production reserves, 2015)
This article gives an analysis of the contents of binary relations in the form of cause-and-effect relationships. It is shown that this form of relationship is the basis for modeling and cognition of the laws of relations among between elements of various systems. At the same time there is shown the possibility of using the relationship in the form of dialectical unity of opposites of categories «single – general» for the discovery of new laws for the systems in the form of organized whole. It has been shown that the principle of forming an organized whole from its parts is the principle of the dialectical unity of opposites of qualitative and quantitative characteristics of their states. There are established rules for the formation and implementation of the activity of an organized whole. It is shown that the fundamental rule of the formation and implementation of the activity of a dialectically organized whole, and also its cognition, is the rule of duality. Cognition of a dialectical by organized whole is only possible by simultaneously exploring ways of forming characteristics of the states of its parts, and the mechanism of realization of its integrated activity. The possibility and necessity of introduction to the set theory of dialectical relationship in the form of «single – general» and an appropriate label for this relationship. This will form the set-theoretic mathematical models for dialectically organized wholes. It is important the rule action for cognition dialectically organized whole. Activity of a dialectically organized whole has a dual character: on the one hand the integrated activity is realized in the form of «unit operations», the result of which is a «philosophical zero», characterized by the category of «general» and on the other hand there is realized the physical process of getting a specific result, characterized by the category of «single».